THE EFFECT OF HALAL LABEL AND FOOD INGREDIENTS TO THE PURCHASING DECISION ON IMPORTED FOOD PRODUCTS (Study On Islamic Economics and Business Faculty Students) - Jumarni Jumarni (Islamic Economic and Business Journal, 2021)
The study discusses the Effect of Halal Label and Food Ingredients to the Purchasing Decision on Imported Food Products on Islamic Economics anda Business Faculty Students. The purpose of this study was to determine the effect halal label and food ingredients to the purchasing decision on imported food products. This study used ex post facto research with an quantitative approach. The population in this study were all students of the Islamic Economics and Business faculty with a sample of 80 respondents. The data collection method used is questionnaire and literature review. The data analysis tool used in this study is multiple linear regression analysis. The results showed that variables of halal label and food ingredients had a significantly positive effect to the purchasing decision on imported food products. The contribution of variable for halal label to purchasing decision is 6% and for variable good ingredients is 9,8%. The contribution of variables for halal label and food ingredients to purchasing decision is 15,4 % and the remaining 84,6% is effected by other variables not used in this study.